PENGARUH SUPERVISI AKADEMIK DAN IKLIM ORGANISASI TERHADAP KEPUASAN KERJA GURU SMP NEGERI DI KABUPATEN TEMANGGUNG DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING - Widi Triana; Arief Yulianto; Asrori (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the influence of academic supervision and organizational climate on job satisfaction of teachers, with work motivation as an intervening variable. The background of the research is based on the phenomenon of low teacher job satisfaction as reflected in limited independent lesson planning, low participation in professional development, and weak motivation. The study employs a quantitative approach with path analysis techniques. The sample comprises 108 public junior high school teachers in Temanggung Regency selected through random sampling. Research instruments were developed based on theories of supervision, organizational climate, motivation, and job satisfaction. The results show that academic supervision and organizational climate significantly affect teacher motivation and job satisfaction. Furthermore, work motivation serves as a significant intervening variable mediating the influence of academic supervision and organizational climate on job satisfaction.